2019
DOI: 10.1111/crj.13018
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effect of smoking on cross‐sectional area of small pulmonary vessel and arterial stiffness in healthy smokers without COPD

Abstract: Introduction Because it induces systemic inflammation, smoking is a risk factor of atherosclerosis and pulmonary hypertension. The brachial‐ankle pulse wave velocity (baPWV) and cross‐sectional area (CSA) of small pulmonary vessels can be useful markers to assess early changes of arterial stiffness and pulmonary vascular alteration in smokers. Objectives This study aimed to explore association between the CSA of small pulmonary vessel and arterial stiffness in healthy male smokers. Methods We enrolled 90 male … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
1
1
2
Order By: Relevance
“…The present study has some limitations, such as the lack of evaluation on tobacco use as a factor of increased arterial stiffness, as previously described [27,28]. However, our data showed that the percentage of smokers was similar between the groups examined.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…The present study has some limitations, such as the lack of evaluation on tobacco use as a factor of increased arterial stiffness, as previously described [27,28]. However, our data showed that the percentage of smokers was similar between the groups examined.…”
Section: Discussioncontrasting
confidence: 48%
“…Atualmente, tem-se conhecimento de ampla gama de fatores que influenciam o estado das artérias e, como consequência, a VOP (12)(13)(14)27,28).…”
Section: Apresentação Do Projetounclassified
See 1 more Smart Citation
“…Moreover, the same research team demonstrated the feasibility of this method in determining whether patients with COPD should undergo right heart catheterization. Besides, Jo et al ( 67 ) suggested that %CSA measurement and pulmonary small vessel changes have the theoretical potential for useful diagnostic applications aimed at early-stage assessment of COPD with pulmonary hypertension. In addition, COPD patients with emphysema and functional small-airway disorders may have a correlation between the total pulmonary vascular volume (TPVV), as measured by CT, and exercise-induced dyspnea symptoms.…”
Section: Ct Quantification Of Pulmonary Vascular Injurymentioning
confidence: 99%